Ultrasonographic Assessment of the Distance of Sciatic Nerve Bifurcation from the Popliteal Crease and its Depth from Skin in Volunteers - Shrestha, U.; Lama Moktan, S.; Shrestha, S.B (Kathmandu University Medical Journal, 2020)
Background Sciatic nerve block used for various surgeries below knee and for maintenance of analgesia demonstrates wide variability regarding its bifurcation into tibial and common peroneal nerves, frequently accounting for incomplete nerve blocks.Objective To determine the variation of sciatic nerve bifurcation among Nepalese volunteers.Method This cross sectional study was conducted in the Department of Anesthesiology of Kathmandu Medical College Teaching Hospital from March to May 2019, where 110 healthy volunteers underwent ultrasonography of sciatic nerve starting from popliteal fossa to its bifurcation. The distance between the bifurcation of sciatic nerve from popliteal crease and depth of the nerve at that point from the skin were measured.Result The mean distance at which sciatic nerve bifurcated from the popliteal crease was 5.42 ± 1.37 cm. Most commonly, the sciatic nerve bifurcated at a distance of 5-7 cm from the popliteal crease in 110 limbs (50.45%). However, in 80 limbs (36.69%), the bifurcation was found at less than 5 cm from the popliteal crease. The depth of the nerve from the skin at the point of bifurcation was 1.72 ± 0.54 cm, with results showing it was deeper in females compared to males (p value < 0.001).Conclusion This study showed that though the distance of sciatic nerve bifurcation from the popliteal crease in our study group was coherent with the published literature of 5-12 cm; many volunteers also had this bifurcation at distances less than 5 cm. Females showed nerves to be deeper at the point of bifurcation than males.